2015
DOI: 10.1002/jcp.24884
|View full text |Cite
|
Sign up to set email alerts
|

The anti-spasticity drug baclofen alleviates collagen-induced arthritis and regulates dendritic cells

Abstract: Baclofen is used clinically as a drug that treats spasticity, which is a syndrome characterized by excessive contraction of the muscles and hyperflexia in the central nervous system (CNS), by activating GABA(B) receptors (GABA(B)Rs). Baclofen was recently reported to desensitize chemokine receptors and to suppress inflammation through the activation of GABA(B)Rs. GABA(B)Rs are expressed in various immune cells, but the functions of these receptors in autoimmune diseases remain largely unknown. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Recently, Huang et al [62] demonstrated that baclofen (GABA B R agonist) alleviates CIA. Oral administration of baclofen decreased Th17 cell numbers, and suppressed IL-6 production by DCs.…”
Section: Collagen-induced Arthritis (Cia)mentioning
confidence: 98%
“…Recently, Huang et al [62] demonstrated that baclofen (GABA B R agonist) alleviates CIA. Oral administration of baclofen decreased Th17 cell numbers, and suppressed IL-6 production by DCs.…”
Section: Collagen-induced Arthritis (Cia)mentioning
confidence: 98%
“…GABA-R activation has been shown to inhibit or reverse disease in animal models of type 1 diabetes (T1D) [4, 6, 9, 1214], rheumatoid arthritis [15], and experimental autoimmune encephalomyelitis [16, 17] and to limit inflammation and disease in type 2 diabetes models [1820]. Studies of GABA's protective mechanisms in these disease models revealed that GABA inhibits inflammatory Th1, Th17, and CD8 + responses [4, 6, 9, 1315], as well as antigen-presenting cell function and TNF α production [16, 21, 22]. Thus, GABA-R activation can inhibit inflammation caused by different mechanisms in mice with different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological analysis of lungs from mice that received GABA just after MHV-1 inoculation revealed that three days post-infection these mice had significantly reduced lung inflammation and markers of lung damage relative to that in control mice. There are a number of different biological processes through which GABA treatment may have ameliorated the severity of pneumonitis: 1) GABA can inhibit macrophage and dendritic cell inflammatory activities (13, 29, 46, 47). Likewise, GABA A -R PAMs reduce the numbers of macrophages in broncholavage fluid, lung secretion of inflammatory cytokines, and inflammatory responses by rodent and human macrophages (22, 2731).…”
Section: Discussionmentioning
confidence: 99%